Factors associated with the need for ventilation at birth of neonates weighing ≥2,500 g (Clinics, 2016)
OBJECTIVES: Approximately 20-40% of annual global neonatal deaths occur among infants with birthweights ≥2,500 g, and most of these deaths are associated with intrapartum asphyxia in low- and middle-income countries. This study aims to evaluate the peripartum variables associated with the need for resuscitation at birth of neonates weighing ≥2,500 g. METHOD: This case-control retrospective study was performed on data from all public reference maternity units in the state of Ceará, Northeast Brazil, between March 2009 and March 2010. The subjects were singleton neonates without malformations weighing ≥2,500 g, who required positive-pressure ventilation in the delivery room. The controls had a 1-minute Apgar score of ≥8 and did not undergo resuscitation. Variables associated with positive-pressure ventilation in the delivery room were evaluated via conditional multivariate logistic regression. RESULTS: Of the 2,233 live births with birth weights ≥2,500 g, 1-minute Apgar scores ≤7, and no malformations, 402 patients met the inclusion criteria, and they were paired with 402 controls. Risk variables for positive-pressure ventilation at birth were a gestational age